Respiratory Morbidity in Children with Repaired Congenital Esophageal Atresia with or without Tracheoesophageal Fistula - Patria, Maria Francesca (Int J Environ Res Public Health, 2017)
Congenital esophageal atresia with or without tracheoesophageal fistula (CEA ± TEF) is a relatively common malformation that occurs in 1 of 2500–4500 live births. Despite the refinement of surgical techniques, a considerable proportion of children experience short- and long-term respiratory complications, which can significantly affect their health through adulthood. This review focuses on the underlying mechanisms and clinical presentation of respiratory morbidity in children with repaired CEA ± TEF. The reasons for the short-term pulmonary impairments are multifactorial and related to the surgical complications, such as anastomotic leaks, stenosis, and recurrence of fistula. Long-term respiratory morbidity is grouped into four categories according to the body section or function mainly involved: upper respiratory tract, lower respiratory tract, gastrointestinal tract, and aspiration and dysphagia. The reasons for the persistence of respiratory morbidity to adulthood are not univocal. The malformation itself, the acquired damage after the surgical repair, various co-morbidities, and the recurrence of lower respiratory tract infections at an early age can contribute to pulmonary impairment. Nevertheless, other conditions, including smoking habits and, in particular, atopy can play a role in the recurrence of infections. In conclusion, our manuscript shows that most children born with CEA ± TEF survive into adulthood, but many comorbidities, mainly esophageal and respiratory issues, may persist. The pulmonary impairment involves many underlying mechanisms, which begin in the first years of life. Therefore, early detection and management of pulmonary morbidity may be important to prevent impairment in pulmonary function and serious long-term complications. To obtain a successful outcome, it is fundamental to ensure a standardized follow-up that must continue until adulthood.